What difference does ("good") HRM make? - Buchan James (BMC, 2004)
Abstract The importance of human resources management (HRM) to the success or failure of health system performance has, until recently, been generally overlooked. In recent years it has been increasingly recognised that getting HR policy and management "right" has to be at the core of any sustainable solution to health system performance. In comparison to the evidence base on health care reform-related issues of health system finance and appropriate purchaser/provider incentive structures, there is very limited information on the HRM dimension or its impact. Despite the limited, but growing, evidence base on the impact of HRM on organisational performance in other sectors, there have been relatively few attempts to assess the implications of this evidence for the health sector. This paper examines this broader evidence base on HRM in other sectors and examines some of the underlying issues related to "good" HRM in the health sector. The paper considers how human resource management (HRM) has been defined and evaluated in other sectors. Essentially there are two sub-themes: how have HRM interventions been defined? and how have the effects of these interventions been measured in order to identify which interventions are most effective? In other words, what is "good" HRM? The paper argues that it is not only the organisational context that differentiates the health sector from many other sectors, in terms of HRM. Many of the measures of organisational performance are also unique. "Performance" in the health sector can be fully assessed only by means of indicators that are sector-specific. These can focus on measures of clinical activity or workload (e.g. staff per occupied bed, or patient acuity measures), on measures of output (e.g. number of patients treated) or, less frequently, on measures of outcome (e.g. mortality rates or rate of post-surgery complications). The paper also stresses the need for a "fit" between the HRM approach and the organisational characteristics, context and priorities, and for recognition that so-called "bundles" of linked and coordinated HRM interventions will be more likely to achieve sustained improvements in organisational performance than single or uncoordinated interventions.